Chloride union recognition by neutral platinum(II) and palladium(II) 5,5'-bis amide substituted bipyridyl receptor molecules - Beer, P; Fletcher, N; Drew, M; Wear, T (1997)
A series of new acyclic platinum(II) and palladium(II) 5,5′-bis-amide substituted 2,2′-bipyridyl receptors have been synthesized and single-crystal structural investigations of two receptors are described. Proton NMR anion binding studies reveal that these neutral receptors recognize chloride anions in dimethyl sulfoxide solution. Copyright © 1996 Elsevier Science Ltd.